The rise of Right-Wing Conservatism in America: Anything new? - Kalimara, Kwame Osagyefo (Prabuddha: Journal of Social Equality, 2020)
“Perhaps the whole root of our trouble, the human trouble, is that we will sacrifice all the beauty of our lives, will imprison ourselves in totems, taboos, crosses, blood sacrifices, steeples, mosques, races, armies, flags, nations, in order to deny the fact of death, which is the only fact we have. It seems to me that one ought to rejoice in the fact of death—ought to decide, indeed, to earn one's death by confronting with passion the conundrum of life. One is responsible to life: It is the small beacon in that terrifying darkness from which we come and to which we shall return. One must negotiate this passage as nobly as possible, for the sake of those who are coming after us.” ~ James Baldwin, The Fire Next Time